Lavender (Lavandula angustifolia) syrup as an adjunct to standard care in patients with mild to moderate COVID-19: An open-label, randomized, controlled clinical trial - Marzieh Gharaaty; Mohsen Bahrami; Sadegh-Ali Azimi; Fataneh Hashem-Dabaghian; Safoora Saberi; Syed Mohd Abbas Zaidi; Amir Hossein Sahebkar; Ayesheh Enayati (Avicenna Journal of Phytomedicine, 2023)
Objective: The ongoing COVID-19 pandemic has been associated with clinical signs characterized by fever, fatigue and cough. Our study aimed to assess the efficacy of a Persian medicine formulation, lavender syrup, as an add-on to standard care in patients with mild to moderate COVID-19.Materials and Methods: In this clinical trial which was conducted in Gorgan (Iran), 84 male and female COVID-19 outpatients were randomly allocated to either lavender syrup receiving 9 ml/twice/day for 21 days with standard conventional care or control groups. The primary objectives were to assess the improvement of clinical symptoms, while the secondary objectives were treatment satisfaction and anxiety levels which were evaluated once a week for 3 weeks.Results: Out of 84 participants, 81 were analyzed (41 in the add-on group). The comparison between groups for cough severity and anosmia showed a higher reduction in the lavender group. The effect size was 0.6 for cough relief. Other symptoms and the Hamilton total score decreased in both groups with no statistically significant differences between the groups. The lavender group showed greater patients’ satisfaction score.Conclusion: Adjunctive therapy with lavender syrup could reduce cough and improve the quality of life in patients with COVID-19 patients.